Microstrip bandwidth enhancement using log periodic technique with inset feed - A. Rahim, Mohamad Kamal (Penerbit UTM Press, 2004)
This paper describes the various techniques to improve the bandwidth of a microstrip antenna. One of the techniques that has been discussed in detail is the log periodic technique. The design, simulation, and fabrication of log periodic antenna (LPA) with inset feed method has been discussed. The antenna has been designed with eleven element array. The performance of the antenna has been investigated in terms of bandwidth, gain relative to a dipole antenna, cross-polar isolation, and beamwidth.